Peningkatan Kemampuan Membaca Bahasa Jerman Melalui Metode Active Learning Tipe Reading Guide - Rahmah Irfan, St Nur; Hasmawati, Hasmawati (Indonesian Journal of Educational Studies, 2018)
The purpose of this study was to obtain data on planning, process, and results of the reading guide type active learning method in students' German reading skills. The data of this study are qualitative data and quantitative data. Qualitative data is obtained through observations and quantitative data obtained through the ability to read the cycle I and cycle II. Data were analyzed using percentage techniques. The results of this study indicate that the reading ability with the percentage value obtained by students in the first cycle reached 66.78% and the second cycle reached 82.14%. These results indicate that the active learning type of reading guide can improve students' reading skills